2014
DOI: 10.1016/j.tem.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and breast cancer pathophysiology

Abstract: Cholesterol is a risk factor for breast cancer although the mechanisms by which this occurs are not well understood. One hypothesis is that dyslipidemia results in increased cholesterol content in cell membranes thus impacting membrane fluidity and subsequent signaling. Additionally, studies demonstrate that the metabolite, 27-hydroxycholesterol (27HC), can function as an estrogen, increasing the proliferation of estrogen receptor positive breast cancer cells. This was unexpected as 27HC and other oxysterols a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 62 publications
2
126
0
3
Order By: Relevance
“…In terms of risk of onset, the role of cholesterol is unclear, further complicated as to whether total, LDL or HDL cholesterol impart risk [35, 66, 67]. Likewise, retrospective analysis of people on statin therapy indicates that these drugs might have conflicting roles in terms of breast cancer onset [68].…”
Section: Impact Of 27hc On the Progression Of Breast And Prostate Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of risk of onset, the role of cholesterol is unclear, further complicated as to whether total, LDL or HDL cholesterol impart risk [35, 66, 67]. Likewise, retrospective analysis of people on statin therapy indicates that these drugs might have conflicting roles in terms of breast cancer onset [68].…”
Section: Impact Of 27hc On the Progression Of Breast And Prostate Cmentioning
confidence: 99%
“…In murine models, a high fat, high cholesterol diet increases breast tumor growth and metastasis [35]. In a more controlled study, it was found that elevating only dietary cholesterol was sufficient to increase tumor growth in MMTV-PyMT mice [74].…”
Section: Impact Of 27hc On the Progression Of Breast And Prostate Cmentioning
confidence: 99%
“…Longer loop regulation is mediated by the liver X receptors (LXRs) which are intracellular receptors of the nuclear receptor superfamily, and which work to eliminate cholesterol through a feed-forward mechanism [74]. Specifically, certain precursors and metabolites of cholesterol such as oxysterols bind to and activate the LXRs, ultimately leading to decreased cellular uptake and increased efflux of cholesterol.…”
Section: Cholesterol Metabolismmentioning
confidence: 99%
“…NR1H2/NR1H3 ligands secreted by tumor cells inhibit CCR7 expression on maturing dendritic cells, impairing immune-surveillance and favoring tumor growth [38]. In mouse breast-cancer models, 27-hydroxycholesterol augments ER-dependent mammary-tumor growth and increases NR1H2/NR1H3-dependent metastasis [39]. The two effects require conversion of cholesterol into 27-hydroxycholesterol by CYP27A1 [40].…”
Section: Lipid-sensorsmentioning
confidence: 99%